L'étoile opéra buffe in three acts - Chabrier, Emmanuel 1841-1894 (Naxos Rights (Europe) Ltd., 2019)
The fanciful story is set in an imaginary kingdom and all, naturally, ends well. However, despite the slight plotline L'Étoile is something of a pivotal work, a unique example of French 19th-century light opera, orchestrated with great sophistication and flooded with gossamer wit. This production, featuring Stephane d'Oustrac, Christophe Mortagne, and Helene Guilmette, is a co-production of the Dutch National Opera, Amsterdam, and Francois Roussillon et Associes
Interpreten unter anderem: Stéphanie D'Oustrac (Lazuli). Christophe Mortagne (Le Roi Ouf I). Hélène Guilmette (La Princesse Laoula). Jérôme Varnier (Siroco). Elliot Madore (Hérisson de Porc-Épic). Julie Boulianne (Aloès). François Piolino (Tapioca). François Soons (Patacha). Residentie Orkest The Hague. Chorus of Dutch National Opera. Patrick Fournillier (Dirigent)
Aufnahme: Amsterdam, Dutch National Opera & Ballet, 13. und 16. Oktober 2014
Bildformat: 16:9
Keywords: Operas; Feature films; Filmed operas; Filmed performances; Concert films; Film; Blu-Ray-Disc